More Than Numbers: The Relationship Between Belonging and Engagement in an Introductory Statistics Course - Catherine Pressimone Beckowski; Benjamin M. Torsney (Journal of Postsecondary Student Success)
More college students from diverse backgrounds and disciplines are enrolling in introductory statistics courses. In these courses, active learning, collaborative projects, and relatable content can help to support student learning, belonging, and engagement. In this study, we examined the effect of student-perceived peer, faculty, and classroom belonging on three dimensions of student engagement in a music-themed introductory statistics course. We identified significant models for each dimension of engagement: absorption (conditional R2 = .76, marginal R2 = .26), dedication (conditional R2 = .81, marginal R2 = .28), and vigor (conditional R2 = .79, marginal R2 = .25). We found significant associations between (a) classroom belonging and dedication, vigor, and absorption, and (b) faculty belonging and absorption. The absorption model demonstrated a significant interaction, with students’ sense of faculty belonging declining over time. Qualitatively, students perceived the course theme, instructors, and peer collaboration as supportive. Implications suggest that instructors can take creative, high-impact approaches to teaching introductory statistics. Fostering students’ engagement and belonging may help to offset students’ anxiety or disinterest and help them to become more autonomous learners.